DEVELOPMENT OF BRAIN-BASED LEARNING MODEL BASED ON PROBLEM-BASED LEARNING (BBL-PBL) TO IMPROVE CRITICAL THINKING AND LEARNING OUTCOMES - Annisatuz Zahro Haryulinda; Jekti Prihatin; Kamalia Fikri (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2020)
The 21st -century learning demands students’ that have critical thinking skills. The learning model of Brain-Based Learning (BBL), combined with the approach of Problem-Based Learning (PBL), is an alternative model that adjusts the critical thinking skils. The objective of this research was to generate a valid, practical, and effective BBL-PBL learning model. This research was research and development using the ADDIE model, consisting of analysis, design, develop, implement, and evaluate. The study was implemented on the tenth-grade students of Rambipuji Senior High School, Jember, Indonesia, in the academic year of 2019/2020. The data collection techniques used were validation of products and test methods, interviews with the teachers, the questionnaire responses of teachers and students, and class observations. The results of the validity of the product were 91.4% as very valid category. The results of the cognitive model’s effectivenest were of 0.81 as high category, the psychomotor aspects were 82 as fair category, and the critical thinking skills were of 85 as excellent category. The practicality results were obtained from the questionnaire responses of the teachers and the students, respectively by 91.2% and 86% which are both excellent categories.